2020
DOI: 10.1124/jpet.119.264481
|View full text |Cite|
|
Sign up to set email alerts
|

Aripiprazole Cytotoxicity Coincides with Activation of the Unfolded Protein Response in Human Hepatic Cells

Abstract: Schizophrenia is a mental disease that results in decreased life expectancy and well-being by promoting obesity and sedentary lifestyles. Schizophrenia is treated by antipsychotic drugs. Although the second-generation antipsychotics (SGA), Olanzapine and Aripiprazole, are more effective in treating schizophrenia, they display a higher risk of metabolic side effects, mostly by development of diabetes and insulin resistance, weight gain, and dyslipidemia. Endoplasmic reticulum (ER) stress is induced when ER home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Thus, the ROS produced by adding Ari increases the therapeutic effect of IR. Forno et al reported that the cytotoxicity of Ari in human hepatic cells was due to activation of the unfolded protein response 14 . Although the unfolded protein response is a mechanism that is generally induced when endoplasmic reticulum stress occurs, and this stress accompanies the generation of ROS 15,16 , the IR‐sensitizing effect of Ari can be attributed to the enhanced generation of ROS by Ari and IR, although further studies are needed to define the exact mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ROS produced by adding Ari increases the therapeutic effect of IR. Forno et al reported that the cytotoxicity of Ari in human hepatic cells was due to activation of the unfolded protein response 14 . Although the unfolded protein response is a mechanism that is generally induced when endoplasmic reticulum stress occurs, and this stress accompanies the generation of ROS 15,16 , the IR‐sensitizing effect of Ari can be attributed to the enhanced generation of ROS by Ari and IR, although further studies are needed to define the exact mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from INS-1 cells was extracted with Trizol ® reagent (15596026; Thermo Fisher Scientific, USA), and reverse transcription was performed using a High-Capacity cDNA Reverse Transcription Kit (436881; Thermo Fisher Scientific, USA) using random primers and Superscript III enzyme (18080093; Thermo Fisher Scientific; USA) according to the manufacturer’s instructions. RT-PCR was used for the detection of XBP1 mRNA splicing with forward (5′-CCTTGTAATTGAGAACCAGG-3′) and reverse (5′-CCAAAAGGATATCAGACTCGG-3′) primers as described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since calcium homeostasis is pivotal in ER stress and mitochondria-mediated cell death, several studies applied Ca 2+ -induced cell death to cancer treatment, including melanoma treatments such as luteolin, N-acetyl-S-(p-chlorophenylcarbamoyl) cysteine (NACC), and sanguinarine [107,117,118], which mechanically revealed their potential pathways. In particular, aripiprazole is not only an antipsychotic drug but a compound capable of depleting ER calcium in melanoma, thereby leading to activation of the unfolded protein response via protein kinase R-like ER kinase (PERK) and inositol-requiring enzyme 1 [119]. Another study found that the anti-tumor effects of polyphenols was also mediated by PERK-directed Ca 2+ release [120].…”
Section: Targeting Calcium Mitochondria and Er Stress In Melanomamentioning
confidence: 99%